(untitled) (Itinera, 2017)
When Martin Crimp’s The Country was first performed at London’s Royal Court Theatre in 2000, critics focused on its Pinterian echoes, the popular motif of betrayal, as well as its attack on the rural myth, and described it as a disturbing and ambiguous play. Despite its unsettling elusiveness and coolness, The Country is a hot piece, in which sensual and sexual tensions permeate chilling verbal exchanges between cryptic – and seemingly unemotional – characters. Staging an intricate web of sensory reactions, provoked by the (im)materiality of language and the evocative potential of props, this drama effectively «works through affective nuances […], acoustic and visual, which develop an almost haunting presence in their absence» (Angelaki 2012: 97). Examining Crimp’s sensory landscapes and his subtle dialogue between presence and absence, this article aims to demonstrate how, in an opaque play built on ellipses, the body sous rature speaks as loud as the ostended body.